KETAHANAN PANGAN RUMAH TANGGA NELAYAN DI KECAMATAN TELUK BETUNG SELATAN KOTA BANDAR LAMPUNG - Pramita Yuliana; Wan Abbas Zakaria; Rabiatul Adawiyah (Lampung University, 2013)
This research aimed to determine the food security and its affecting factors among fisherman households. This research was held in Kangkung Village,Teluk Betung Selatan Subdistrict of Bandar Lampung City using a survey method. Fifty one respondents of fisherman household were chosen by a simple random sampling. Household food security was valued by the segment of food expenditure, the energy sufficiency level, and the protein sufficiency level. The factors which were estimated affect the food security were analyzed by logistical method. The research result showed that : (1) the food security of the fisherman household in Kangkung Village,Teluk Betung Selatan Subdistrict, Bandar Lampung City was categorized as food resistant (56,86%) and food insecurity (43,14%); (2) the household number, household expenditure, and housewives’ nutrition knowledge affected the household food security of the fisherman in Kangkung Village, Teluk Betung Selatan knowledge. Keywords: food security, fisherman, food resistant, food insecurity, household